Gender Dysphoria And Trauma Towards Main Character In I Wish You All The Best Novel By Mason Deaver - Stanley Novaldo; Sayyid Khairunas (Journal of Applied Linguistics, 2024)
This study aimed to analyze gender dysphoria and trauma in Ben de Backer, who is the main character of Mason Deaver's novel entitled I Wish You All the Best. This novel tells the ups and downs in the life of Ben de Backer a non-binary who is still underage. The object of this study is to analyze the symptoms of gender dysphoria and trauma in a non-binary student, in this case, Ben de Backer, and provide an overview of mental issues as well as gender and sexuality for readers. In theory, the researcher wishes to develop theoretical knowledge of literature related to gender and mental health. Practically, this research is useful as a reference for readers who will carry out similar research, especially in terms of gender dysphoria and trauma in other literary works. This research is included in the type of literary criticism because the writer interprets and analyzes a literary work, especially a novel. The data in this study were taken directly through quotations from the novel, as well as from various other sources. The results of this study showed that gender dysphoria and trauma exist and have real impacts on human beings. Gender dysphoria can cause trauma if the response to the problem is rejection, which can lead to other major problems, such as anxiety, eating disorders, and depression Keywords : Gender Dysphoria; Trauma; Literature